2016
DOI: 10.1002/tqem.21480
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Environmental Hazards and Health Effects of Pollution in Developing Countries: A Case Study of Nigeria

Abstract: Pollution has taken on a global dimension, and the effects are most obvious in developing countries. The effects take a toll on human health, animals, and vegetation, as well as on soil, air, and water quality. The objective of this article is to discuss the current relationships among pollution, environmental quality, and human health within the frame of anthropogenic activities in developing countries. In addition to personal observations, we review relevant literature on conditions throughout the developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 83 publications
(65 reference statements)
1
40
0
Order By: Relevance
“…Approximately 7,310 t have reached their end of life, with 2,190 t having been recycled and 5,120 t disposed of in dumps. Currently, approximately 7,000 t of MPs (approximately 87.5 million MPs) are imported into Nigeria per year (Babayemi et al., ).…”
Section: E‐wastementioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 7,310 t have reached their end of life, with 2,190 t having been recycled and 5,120 t disposed of in dumps. Currently, approximately 7,000 t of MPs (approximately 87.5 million MPs) are imported into Nigeria per year (Babayemi et al., ).…”
Section: E‐wastementioning
confidence: 99%
“…In Nigeria, metals recovery activities are actively going on, with a massive transport of scrap metals to relevant industries for recycling ( Exhibit ). Despite these efforts, millions of EoL motor vehicles in the country are yet to be collected for the recovery of scrap metals (Agbo, ; Babayemi et al., ). Recent studies have shown that the average weight of a saloon or sedan car is 1,250 kg (Agbo, ), and of this 81% is metal ( Exhibit ).…”
Section: Waste From the Transportation Sectormentioning
confidence: 99%
See 2 more Smart Citations
“…Human health effects of cadmium include genetic disorders, cancer, impairment of renal function, bronchiolitis, a decrease in hemoglobin level, etc (Cabral et al, 2015;Cartularo et al, 2015;Zang, 2016). Cadmium may cause nasal irritations, cancer, bronchitis and ulcerations of the septum, decreased pulmonary function, etc (Shanker and Venkateswarlu, 2011;Babayemi et al, 2016). These toxic elements find their way into the environment usually as a result of pollution arising from human activities, and consequently, contaminate the different environmental media on which human life depends.…”
mentioning
confidence: 99%